An applied framework to estimate the direct economic impact of Marine Spatial Planning - Surís-Regueiro, Juan C.; Santiago, José L.; González-Martínez, Xosé M.; Garza-Gil, M. Dolores (Marine policy, 2021)
The complex nature of the Marine Spatial Planning (MSP) requires the integration and consideration of multiple elements, ranging from the ecological and environmental to the socio-economic as well as the political, institutional or cultural. To succeed, the public policies demand techniques and tools that allow to evaluate the effects or impacts on the society. By applying an empirical approach, this paper presents a framework to evaluate the direct economic impacts linked to the implementation of MSP policies in three case studies: Belgium, Germany and Norway. The methodological procedure is sequenced in 4 phases: identification of the sectors involved, data collection, construction of counterfactual scenarios and estimate of impacts after consulting the stakeholders. With the application of this framework to the case studies, an estimate was made of the variations in the value of production for each marine sector that can be directly attributed to the implementation of the MSP. In general, they were positive in the three cases analysed. In the medium scenario, cumulative final direct impacts of € 1875 million were estimated in the German case (2010–2016 period), € 929 million in the Belgian case (2014–2016) and € 2262 million in the Norwegian case (2013–2016). These results can serve as the basis for further estimations of indirect and induced impacts of the implementation of spatial management policies in a blue economy context. •Methodological stepwise procedure for estimating economic impacts related to public policies.•Estimate of direct economic impacts of Marine Spatial Planning by sectors of the blue economy.•Direct economic impact of Marine Spatial Planning in Belgium, Germany and Norway.